Pattern of Head injuries in Homicidal deaths at Jaipur During 2012-13, India: An Autopsy based Study - Punia, R K; Yadav, Anil; Lalchand (Journal of Indian Academy of Forensic Medicine, 2014)
Inflicting injury to the head is one of the most effective methods of homicide. The aim of the present study was to evaluate the pattern of head injury among homicidal death victims. In present study 72 cases of homicidal deaths were studied. Males were victimized Three and half times more than females. Majority of cases were in 21-40 years of age comprising of 34 cases (47.43%). Majority of victims were married in 55 cases (76.38%). Injuries were inflicted by blunt weapons in significant number of cases; 48 cases (66.67%) which were followed by injuries by sharp weapons in 14 cases (19.45%). The skull was fractured in 75% of victims. Most common pattern observed was combination of SDH & SAH along with skull fracture in 32 cases (44.44%). The majority of the victims (55.5%) died instantly or within 24 hours. Defense wound were present in 47.2% of the victims. The information gained from this type of analysis can be used by law enforcement authorities to curtail the amount of violence present in today’s society.